PENGGUNAAN MODEL PEMBELAJARAN MAKE A MATCH BERBANTUKAN MEDIA KARTU PECAHAN UNTUK MENINGKATKAN KETUNTASAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS III SDN PILANGBANGO - Edita, Ovilia; Ardhi, Muh. Waskito; Hartuti, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is Classroom Action Research (PTK). The subjects of this research were class III students at SDN Pilangbango, Kec. Kartoharjo Madiun City for the 2023/2024 Academic Year with a total of 20 students, consisting of 14 male students and 6 female students. The time of this research was March 2024. In class III of SDN Pilangbango there were 14 children who received learning outcomes below the KKM, so there were 70% of students who still had difficulty in fractions. This problem can be overcome by using the make a match learning model using fraction cards. In the pre-cycle, the class average was 67. At this stage, in cycle 1, using make a match learning with fractional card media, the class average was 72, which experienced an increase of 7.46%. In cycle 2 the student class average was 92.5 which experienced an increase of 28.47%. Teacher and student activity also increased from cycle I to cycle II, increasing student activity by 33.3% from 60% to 80% and teacher activity increased by 6.9% from 86% to 92%. Because the desired indicators have been achieved in the second cycle, it is declared successful and corrective actions are stopped.